REVIEW OF HUMAN RESOURCE MANAGERS PROBLEMS IN INDIAN CONTEXT - Sharma, Ms. Rajnil (IJRDO - Journal of Business Management, 2016)
HR managers are facing many challenges in present business scenario like Globalization workforce diversity, technological advances and changes in political and legal environment change in information technology. All these challenges increase the pressure on HR managers to attract, retain and nurture talented employee. HR professional can’t ignore these challenges rather they ought to be line to design and execute innovative mechanisms of developing skills and competencies of human resources to prepare them to accept the emerging challenges. With the advent of the IT revolution all over the world and globalization being the new mantra across the corporate sector, the Human Resource Management practices and policies have undergone severe changes. The challenges that are faced by the HRM today are totally new to what has been few years ago. This paper focuses on the challenges that are affecting the organizations all over the world.